2019
DOI: 10.1371/journal.pone.0213420
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals that fertilization with cryopreserved sperm downregulates genes relevant for early embryo development in the horse

Abstract: Artificial insemination with cryopreserved spermatozoa is a major assisted reproductive technology in many species. In horses, as in humans, insemination with cryopreserved sperm is associated with lower pregnancy rates than those for fresh sperm, however, direct effects of sperm cryopreservation on the development of resulting embryos are largely unexplored. The aim of this study was to investigate differences in gene expression between embryos resulting from fertilization with fresh or cryopreserved sperm. E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…In addition, sublethal levels of oxidative stress are known to impact the integrity of sperm DNA thereby influencing the potential development of the embryo and the health and wellbeing of the offspring (Aitken et al 1998a, Aitken & Curry 2011. For example, the altered patterns of gene expression observed in equine embryos as a consequence of insemination with cryostored spermatozoa maybe a case in point, because cryostorage is known to be associated with the induction of oxidative DNA damage (Thomson et al 2009, Ortiz-Rodriguez et al 2019.…”
Section: Redox Regulation Of Sperm Function -The Yin and The Yangmentioning
confidence: 99%
“…In addition, sublethal levels of oxidative stress are known to impact the integrity of sperm DNA thereby influencing the potential development of the embryo and the health and wellbeing of the offspring (Aitken et al 1998a, Aitken & Curry 2011. For example, the altered patterns of gene expression observed in equine embryos as a consequence of insemination with cryostored spermatozoa maybe a case in point, because cryostorage is known to be associated with the induction of oxidative DNA damage (Thomson et al 2009, Ortiz-Rodriguez et al 2019.…”
Section: Redox Regulation Of Sperm Function -The Yin and The Yangmentioning
confidence: 99%
“…In horses, sperm cryopreservation increased global DNA methylation [77], whereas in boar sperm, freezing-thawing decreased the relative abundance of mRNAs as well as the protein levels of some genes associated with DNA methylation (DNMT3A, DNMT3B), histone modifications (JHDM2A, KAT8) and genomic imprinting (IGF2) [78]. Recently, a comparative transcriptome analysis of embryos obtained with fresh and cryopreserved stallion sperm revealed that several sperm mRNA transcripts with a relevant function in early embryo development were downregulated after cryopreservation [79]. However, there is a lack of similar studies in ruminant species.…”
Section: Molecular Changes In the Sperm Chromatin During Cryopreservamentioning
confidence: 99%
“…Animal studies indicate that fecundation with spermatozoa experiencing oxidative stress may cause embryonic death [203], an effect that has been linked to oxidative damage in the spermatozoa [204]. Recent research from our laboratory has compared the effect of cryopreservation on the transcriptome of early equine embryos [205]. Using the same ejaculate, half processed as fresh sperm and the other half frozen and thawed, we obtained embryos from the same mare and stallion after artificial insemination with the aliquot of fresh sperm and, in the mare’s next cycle using the frozen thawed semen aliquot.…”
Section: Impact Of Early Embryo Development (Eed)mentioning
confidence: 99%
“…Significant downregulation of genes involved in biological pathways related to the gene ontology (GO) terms oxidative phosphorylation, DNA binding, DNA replication, and immune response . Interestingly, many genes with reduced expression were orthologs of genes in which knockouts are embryonic lethal in mice [205]. While the exact mechanism behind these changes remains to be elucidated, redox deregulation and oxidative stress in the spermatozoa seem to be an important factor.…”
Section: Impact Of Early Embryo Development (Eed)mentioning
confidence: 99%
See 1 more Smart Citation